Procedural Justice, Organizational Trust, Organizational Identification dan Pengaruhnya pada Employee Engagement - Praptini Yulianti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
Employee engagement in the workplace is very important, especially for the organizational competitive advantage. Workplace procedural justice is an important motivator for employee work attitude and performance. Employee engagement in the workplace can be built through procedural justice, organizational trust  and organizational Identification. This research is an explanatory research that will explain the causal relationship between variables or through hypothesis testing. The sample in this study was collected through 100 respondents. The criteria of the selected respondents were the ones that working in the production division, since production division is the core of industrial companies. The sampling technique in this study used Partial Least Square. The results of this study supports that organizational trust and organizational identification  as  mediator  the relationship  of procedural justice and employee engagement